The short story a very short introduction - Kahn, Andrew ca. 20./21. Jh (Very short introductions, 2021)
Drawing on examples from across the globe and throughout history, Andrew Kahn explores the key characteristics of the short story. He shows how its rise was intertwined with international print culture, and discusses the essential techniques within this thriving literary genre, as well as the ways in which it is constantly innovated, even today